Pengembangan Kewirausahaan Ecoprint Berbasis Smart Steamer Machine Guna Meningkatkan Kualitas Produk dan Efisiensi - Rahmawati, Yuni; Irianti, Agus Hery Supadmi; Sujito, Sujito; Hidayat, Rachmad; Soesetio, Yuli; Mufti, Aya Shofia (Bulletin of Community Engagement, 2023)
Ecoprint, a fabric printing and dyeing technique utilizing natural dyes with leaves, is currently experiencing a surge in demand and becoming a trend among fashion entrepreneurs and textile craftsmen. The unique patterns created from leaves distinguish ecoprint from traditional batik designs in the market, making it highly appealing. Apietz Craft, a Small and Medium Enterprise (SME), was established at the beginning of 2020 during the Covid-19 pandemic. Mostly operated by residents of Jl. Hasyim Ashari II, Sepanjang Village, Gondanglegi District, Malang Regency, the business faced challenges during the ecoprint fabric steaming process. The issues stemmed from the small size of the steaming pot and the lack of temperature control, leading to a decline in fabric quality. These obstacles hindered the ecoprint production process, resulting in suboptimal outcomes. In response to these challenges, this PKM program proposes a solution by introducing a technology transfer initiative. A smart steamer machine will be implemented, designed to accommodate a larger capacity and capable of monitoring temperature within the machine. This advancement aims to enhance production quality and improve production efficiency. The initiative is expected to address the current issues faced by our partner, enabling them to achieve optimal ecoprint fabric production. Keywords: Smart Steamer Machine, Ecoprint, Development Entrepreneurship